Commuting Toeplitz and Hankel Operators on Harmonic Dirichlet Spaces - Qian Ding; Yong Chen; Yufeng Lu (Journal of Function Spaces)
On the harmonic Dirichlet space of the unit disk, the commutativity of Toeplitz and Hankel operators is studied. We obtain characterizations of commuting Toeplitz and Hankel operators and essentially commuting (semicommuting) Toeplitz and Hankel operators with general symbols.